ADM1 Parameter Calibration Method based on partial least squares regression framework for industrial-scale anaerobic digestion modelling - Xu, Zhehua (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.